Conditionality and the needs of developing countries - Graham Bird (Intereconomics, 1982)
The principal cause of the balance of payments deficits of the non-oil developing countries has altered since 1973: exogenous factors now play a far more important role than previously. The appropriateness of the conditions conventionally attached to IMF drawings needs to be re-examined in this light.
Keywords: 330; IMF